Graph centrality of BRCA1 in Protein-Protein Interaction network: An Overview (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cancer is a leading cause of death and around 10 million people died in 2020. In terms of new cases reported in 2020, leading was breast cancer with 2.26 billion cases.  In most cases, reason for the disease is stated as a germline mutation on tumor suppressor gene, BRCA1. Even though dysfunction of BRCA1 is the reason for cancer development, the pathway determining this malignant cellular transformation is poorly defined. Identifying the mechanism behind functional loss of this proteins is one of the major challenges faced by cancer biologists. This paper makes an attempt to characterize the behavior of BRCA1 by identifying its topological properties in a Protein-Protein Interaction Network (PIN). .